A rapid and cost effective ultrasonic solvent extraction method for determination of λ-cyhalothrin and cypermethrin residues in soil - Zulhilmi, Z.A.M.; Bakar, N.K.A.; Muhamad, H.; Zainudin, B.H. (Lembaga Minyak Sawit Malaysia, 2015)
An effective, simple, and cost effective ultrasonic solvent extraction procedure was developed for the determination of λ-cyhalothrin and cypermethrin residues in soil by gas chromatography with electron capture detector (GC-ECD). Several extraction parameters were optimised with regard to the solvent type, solvent volume and duration of sonication. Under the optimum conditions, recovery studies were performed at five fortification levels (0.01, 0.02, 0.05, 0.1 μg g-1). The recovery level ranged from 93.99% to 101.49% and 90.59% to 99.50% for λ-cyhalothrin and cypermethrin respectively. The relative standard deviation values were less than 4% in all cases. The sensitivitiy of the method was acceptable with limits of detection (LOD) of 0.0025 μg g-1 and 0.01 μg g-1 for λ-cyhalothrin and cypermethrin, respectively. Finally, the proposed method was applied successfully for residue determination of both λ-cyhalothrin and cypermethrin in soil samples from an oil palm plantation in Labu, Negeri Sembilan, Malaysia.